2010
DOI: 10.1007/s11123-010-0184-0
|View full text |Cite
|
Sign up to set email alerts
|

Fractional regression models for second stage DEA efficiency analyses

Abstract: Data envelopment analysis (DEA) is commonly used to measure the relative efficiency of decision-making units. Often, in a second stage, a regression model is estimated to relate DEA efficiency scores to exogenous factors. In this paper, we argue that the traditional linear or tobit approaches to second-stage DEA analysis do not constitute a reasonable data-generating process for DEA scores. Under the assumption that DEA scores can be treated as descriptive measures of the relative performance of units in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
211
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(238 citation statements)
references
References 36 publications
4
211
0
4
Order By: Relevance
“…The DEA model of data analysis with regard to bank efficiency has generally been favoured by most academics (Berger et al, 1993;Berger & Humphrey, 1997;Casu & Molyneux, 2000). Despite criticism from some academics (Simar & Wilson, 2011;Ramalho, Ramalho & Henriques, 2010) it is generally accepted by most academics that the DEA model is a sound technique for efficiency estimation. McDonald (2009) examined the second stage DEA efficiency analyses and found that there are good arguments for treating DEA efficiency scores as descriptive measures in a second stage analyses.…”
Section: Efficiency Estimationmentioning
confidence: 99%
“…The DEA model of data analysis with regard to bank efficiency has generally been favoured by most academics (Berger et al, 1993;Berger & Humphrey, 1997;Casu & Molyneux, 2000). Despite criticism from some academics (Simar & Wilson, 2011;Ramalho, Ramalho & Henriques, 2010) it is generally accepted by most academics that the DEA model is a sound technique for efficiency estimation. McDonald (2009) examined the second stage DEA efficiency analyses and found that there are good arguments for treating DEA efficiency scores as descriptive measures in a second stage analyses.…”
Section: Efficiency Estimationmentioning
confidence: 99%
“…First, select one index from the four using factor analysis [20]. The second involves modelling each of the indices, testing each of them through inspection of model properties and rigorous tests such as P test, in order to first select the most appropriate functional form for each index, and then choose the best model from among the four selected models as the most appropriate model [10,36]. The effort involved in the latter which provides the same results as the former makes the former appear more efficient than the latter; hence, the former approach was selected for this study.…”
Section: Diversification Indexmentioning
confidence: 99%
“…We follow Ramalho et al [36] by testing four functional forms in order to select one (best-bet) for discussion.…”
Section: Fractional Regression Modellingmentioning
confidence: 99%
See 2 more Smart Citations